2020
DOI: 10.1063/5.0010771
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the different sources of stress acting in fully rough turbulent flows over geometrical roughness elements

Abstract: The discrete element roughness method is considered in this article for the prediction of turbulent flows over rough walls. This approach is derived by ensemble- and volume-averaging the Navier–Stokes equations, providing double-averaged Navier–Stokes equations, and yielding three unknown terms in the momentum equation: the Reynolds stress and dispersive stress tensors and the average drag force acting on the roughness elements. This work aims at analyzing these different terms, quantifying their respective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Compared with a smooth surface, a significant upward shift of the logarithmic region in the surfaces of sample B and sample G is observed over two bulk Reynold numbers Re b . This is in agreement with the experimental result of Toussaint et al , The offset distance is denoted by −Δ U + . The detailed surface properties are summarized in Table ; when −Δ U + is negative, the velocity distribution shifts downward, and the drag is greater than the corresponding smooth wall.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Compared with a smooth surface, a significant upward shift of the logarithmic region in the surfaces of sample B and sample G is observed over two bulk Reynold numbers Re b . This is in agreement with the experimental result of Toussaint et al , The offset distance is denoted by −Δ U + . The detailed surface properties are summarized in Table ; when −Δ U + is negative, the velocity distribution shifts downward, and the drag is greater than the corresponding smooth wall.…”
Section: Resultssupporting
confidence: 92%
“…Not only are tiny spines scattered on the surface of the pufferfish, but the stout rounded bodies of the fish are discovered to be also covered with small spines. 13 Toussaint et al 14 utilized numerical simulation to analyze the roughness elements (hemisphere, cylinder, and truncated cone) in the turbulent flow and found that the virtual origin of the rough surface of the cone shape (the height of the average roughness drag) is lower than the others. Chen and Martinuzzi 15 and Taylor and Martinuzzi 16 presented statistics on the speed around the cone in the open wind tunnel, observed the vortex shedding period in the cone, and proposed that the counter-rotating base vortices that were stretched repeatedly appeared behind the cone.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Normalized number u + = u / u τ and y + = y ′ u * /ν where y ′ is corrected with the roughness offset y 0 . κ is the Kármán constant (κ = 0.4), B is the smooth-wall intercept ( B = 5.5), ν is kinematic viscosity (ν = 1.011 × 10 –6 at a water temperature of 20 °C), and Δ U + is the roughness function which is variable-dependent on the wall situation. For the smooth wall, Δ U + and y 0 is zero and the log-law region is described by equation u / u * = 2.55 ln ( yu τ /ν) + 5.5.…”
Section: Results and Discussionmentioning
confidence: 99%
“…[ 191 ] Toussaint et al used a two‐component LDV system to measure the velocity components of the flow direction and wall normal. [ 192 ] Flack et al explored the influence of surface roughness skewness on fluid drag by two‐component LDV. The results showed that the surface friction drag tends to increase with increasing deflection.…”
Section: Experimental Methods For Measuring Drag Reductionmentioning
confidence: 99%